The Methodology of Abdullah Jahangir in Challenging ‎Christianity in Bangladesh - Md Helal Uddin; Md Maruf Hasan (Journal of Comparative Study of Religions, 2022)
Professor Dr. Abdullah Jahangir is considered as one of the important prominent Islamic figures in Bangladesh for his various writings, lectures, and social activities. Due to his critical approach in writings and lectures, he is not only well-known in Bangladesh but also in India among Bengali native speaking people. On Islam and comparative Religion, he had outstanding knowledge and contribution as to provide solutions for existing problems in the context of Indian subcontinent. This paper aims to explore the methodology of Abdullah Jahangir in the study of Christianity with special reference to his master piece Pobitra Bible Porichiti O Porjalochona. The research is based on qualitative in nature method will be used in this article and to examine the methodology of Abdullah Jahangir to understand how he studied and viewed about Christianity especially Bible in the context of Indian subcontinent. The outcomes of this research will enhance new outlook in the field of comparative religion and improve our understanding in the study of religious studies. The outcomes of this research will enhance new outlook in the field of comparative religion and improve our understanding in the study of religious studies.